A history of Christianity - MacCulloch, Diarmaid 1951-; Bancroft, Gillian; Salt, Siân ([London] BBC Worldwide, 2010)
"In this fascinating series Profesor MacCulloch explains how Christianity first spread east, extending into Syria, Central Asia, India, and the Far East. He explores the extraordinary and unpredictable rise of the largest single body of Christian devotion in the world, the Roman Catholic Church, and reveals how confession was invented by monks in a remote island off the coast of Ireland. As the series progresses it charts Eastern Orthodox Christianity's fight for survival after its glory days in the eastern Roman Empire and looks at the Reformation and rise of Protestantism as well as the evangelical revial and the American-led rise of Pentecostalism" (container).
Exempt from classification
GB 1996
Sprache: engl. - Untertitel: engl. für Hörgeschädigte
Keywords: DVD-Video